Transmedia Storytelling na Televisão Portuguesa - o Caso de Estudo da Visita Guiada - Maria do Carmo Azevedo Meireles (2015)
Transmedia storytelling has been explored in countries like USA, Brazil, UK and France. It is fundamental to understand what transmedia storytelling can bring to the Portuguese television and in what way it can influence the audience of a certain show. Within this context, a transmedia project was created for the RTP show Visita Guiada. This show is an historical show that is concerned with letting Portuguese viewers be aware of the national cultural heritage. The transmedia project - Diário do Henrique -would reinforce the show's goal of cultural propagation through the adaption of the show's contents to a young aged group. To start developing Diário do Henrique, a study of the show and the possible platforms to be created was made. From the results of this study, a transmedia bible was created. Finally, the project would conclude with a collaborative implementation of the transmedia project with RTP. Despite the existing limitations, the project was able to follow the show's second season and implement the proposed platforms: Herique Magalhães' facebook, the Diário de Viagens a Portugal blog, the posters (to advertise the project and the contest), the Diário do Henrique e-book and website, and two videogames, Henrique VS Mega-Ratazana and A última história. The research methodology involved the analysis of the case studies and subsequent development and implementation of the transmedia project Diario do Henrique. At the end of the project, statistic data was gathered from the platforms. A questionnaire was also made to understand the behavior of the audience during the project and in which way Diário do Henrique was able (or not) to increase the age group and audience of Visita Guiada. From the final results, it could be seen that the project platforms did not manage to create a good link with Visita Guiada's already existing platforms: the age group targeted for the project was attracted to the project but not to the show and to its platforms, failing to increase the show's audience. The study of transmedia storytelling in the context of national television is essencial to understand in what ways transmedia can work in the diverse television shows and in different population sectors. This is fundamental especially when the television shows are though from the beginning to be transmedia projects.